FINANCIAL MECHANISMS FOR SUPPORTING INNOVATION AND INVESTMENT DEVELOPMENT OF AGRO-INDUSTRIAL ENTERPRISES (Development Service Industry Management, 2024)
This article is devoted to the study of key aspects of constructing financial mechanisms to support the innovation and investment development of agro-industrial enterprises. The purpose of the study is to analyze, systematize, generalize, and improve the existing theoretical and methodological framework for forming a financial mechanism to support this development.Key theoretical aspects of forming the financial mechanism for agro-industrial enterprises' innovation and investment development as a strategic component of Ukraine's economy are considered. The study substantiates the necessity of forming a comprehensive financial mechanism, including venture financing, agricultural receipts, state grants, and preferential loan programs, to ensure sustainable enterprise development. The article examines agro-industrial enterprises' innovation and investment development as an essential component of enhancing their competitiveness, ensuring food security, and achieving environmental sustainability. Fundamental problems that limit innovation and investment development in the agro-industrial sector have been identified, including a low level of investment activity, limited access to modern technologies, and insufficient state support for innovations. A financial mechanism to support innovation and investment development of agro-industrial enterprises is proposed. Its distinctive feature is comprehensiveness, integrating various funding sources, risk management tools, and mechanisms for adapting to changes in the external environment. Integrating public, private, and international support creates a synergistic effect, increasing the efficiency of resource mobilization for innovative activities. According to its flexibility and adaptability, the proposed mechanism contributes to enterprise stability in a volatile economic environment while simultaneously stimulating the modernization of the agro-industrial complex. It is determined that creating favorable conditions for innovation and investment activities requires an integrated approach, including the development of public-private partnerships, improving state support programs, and expanding access to international financial resources.
Keywords: financial mechanism; innovation and investment development; agro-industrial enterprises; funding sources; risk management; sustainable development